Tobacco Dependence: Nursing Care Plans - Aurora Miguel García; Federico de Miguel Salinas (Fundación para el Desarrollo de la Enfermería, 2009)
Tobacco dependence is a major risk factor for health that requires a correct approach by all health workers. Nursing plays a key role both in identifying smokers, as in the systematic advice to quit smoking, or assist in smoking quit. This work presents three standardized care plans that enable the nursing work in accordance with a methodology and using a standardized language that allows both continuity of care such as research and development of knowledge nurse: Care plan to smoker in precontemplation stage; Care plan to smoker in contemplation stage; Care plan to smoker in preparation/action stage.